Efektivitas Pelatihan dan Pembinaan Nazir Dalam Meningkatkan Wakaf Produktif - Alkaf, Aisyah; Usman, Rafika; Y, Yunita (Media Hukum Indonesia (MHI), 2025)
Productive waqf plays a strategic role in supporting the sustainable social and economic development of the Muslim community. However, the effectiveness of waqf management still faces challenges, particularly related to the quality and capacity of nazhir as the asset managers. This study aims to assess the impact of training and guidance on nazhir in improving productive waqf management. The method used is a literature review from various scientific sources discussing nazhir training and guidance. The findings indicate that enhancing nazhir capacity through structured training and intensive coaching improves professionalism, transparency, and accountability in waqf management. The Indonesian Waqf Board (BWI) plays a crucial role in conducting training and certification of nazhir, despite challenges such as limited resources and diverse backgrounds among nazhir requiring adaptive and innovative approaches. Training and guidance for nazhir have proven effective in optimizing productive waqf, contributing to economic empowerment and sustainable social welfare in Indonesia.